PENGUATAN MANAJEMEN TRANSFORMASI MENUJU MADRASAH BERMUTU - Safuroh; Nining Syamsi Komariah (Almarhalah: Jurnal Pendidikan Islam, 2023)
Discriminatory policies towards Islamic education during the Dutch Colonial period in Indonesia have led to educational problems in Madrasas to this day, including: Madrasas are isolated from the flow of reform, experiencing management weaknesses, and low in actual quality. As a result, madrasas are conditioned by conventional education, and become the second choice after public schools. The aim of this study is to analyze the transformation from conventional madrasas to quality madrasas, by applying quality management reinforcement. The research method uses a qualitative approach to library research (library research), with theories referred to from several sources, namely, journals, books, and articles, as well as other literature relevant to the theory in the theme of this study, both physical and digital sources, to obtain data. valid, the technique used by the researcher is in the form of content analysis, namely a technique that uses text found in various literature or certain media, then the data is processed, analyzed and finally a conclusion is drawn. The results of the study show that transforming conventional madrasas into quality madrasas requires strengthening in management, commitment and mutual cooperation between educational stakeholders in madrasas and continuing to develop by providing service and satisfaction to all customers. Education in madrasas should emphasize transformational touches to implement professional quality management strengthening in madrasas, so that quality madrasas can be realized.